Beyond Cost-Benefit Analysis in the Governance of Synthetic Biology - Wallach, Wendell (The Hastings Center report, 2018)
For many innovations, oversight fits nicely within existing governance mechanisms; nevertheless, others pose unique public health, environmental, and ethical challenges. Synthetic artemisinin, for example, has many precursors in laboratory-developed drugs that emulate natural forms of the same drug. The policy challenges posed by synthetic artemisinin do not differ significantly in kind from other laboratory-formulated drugs. Synthetic biofuels and gene drives, however, fit less clearly into existing governance structures. How many of the new categories of products require new forms of regulatory oversight, or at least extensive forms of testing, remains unclear. Any effort to improve the governance of synthetic biology should start with a rich understanding of the different possible science-policy interfaces that could help to inform governance. CBA falls into a subset of the overall range of possibilities, and which interface is appropriate may turn out to depend on context, on the demands of the decision at hand. In what follows, we lay out a typology of interfaces. After that, we turn to the question of how to draw upon the range of possible interfaces and effectively address the factual and moral complexities of emerging technologies. We propose a governance model built around structures that we call “governance coordinating committees.” GCCs are intended to be mechanisms for accommodating the complexities of innovations that have far-ranging societal impacts. The production of biofuels, for example, could contaminate water supplies and have a destructive environmental impact if not managed correctly. The introduction of a gene drive could have economic and environmental impacts that are not restricted to one nation. Forging appropriate means for determining and evaluating those societal impacts, to the best of a corporation's, industry's, or government's ability, is central to responsible research and innovation. Public policy must be shaped in a manner that accommodates as many concerns as possible and minimizes risks.